Digital Literacy for Science Teacher’s at Secondary School Level: A Need Assessment Analysis - Tariq Mehmood, Sheikh; Kashif Majeed, Muhammad; Saleem Khan, Ammar (JSE, 2023)
Abstract Literacy has different meanings in different contexts. If you can grasp and use digital technology successfully, you have digital literacy. Throughout the educational process, this applies. A wide range of applications includes civic engagement, pastoral care, and e-safety, among others. To be digitally literate implies knowing how to use the internet, social media, and mobile devices to communicate, study, and work in today's digitally-dependent world. In the digital age, digital literacy refers to a person's capacity to discover, assess, engage, and effectively transmit information through typing and other media on different digital platforms. The study intended to determine how teachers' digital literacy was assessed; to find out science teachers' understanding of information presentation and arrangement. The tool for this research was a questionnaire, and it was quantitative. There were 996 science teachers in all, all of them were secondary school teachers from the district of Muzaffargarh. A questionnaire was used to gather the quantitative data. The acquired data was analyzed by dividing the demographics of the respondents into percentages. Expert opinion and the Cronbach Alpha score were used to verify the questionnaire's validity and reliability during the test's pilot phase in Muzaffargarh district.